Prevailing Economic Conditions and Lecturers’ Productivity, Job Satisfaction, and Job Performance in Nigeria - Eze, Emmanuel Chukwuma; Okafor, Ikechukwu Giveson (Universal Education Jurnal Teaching and Learning, 2026)
This study examined how prevailing economic conditions relate to productivity, job satisfaction, and job performance of lecturers in public tertiary institutions in Imo State, Nigeria. A correlational survey research design was adopted. Three research questions and three hypotheses guided the study. The population comprised 160 Economics educators from six public tertiary institutions. Four instruments were used to collect data for this study: the Prevailing Economic Condition Questionnaire, Lecturers' Productivity Questionnaire, Job Satisfaction Questionnaire, and Job Performance Questionnaire. Pearson correlation coefficient analyzed relationships, while p-values tested significance. Results revealed that economic conditions had a strongly significant negative relationship with lecturers' productivity (r = -0.75, p < 0.05). Economic conditions showed an insignificant negative weak relationship with job satisfaction (r = -0.10, p > 0.05) and a significant negative moderate relationship with job performance (r = -0.62, p < 0.05). Findings indicate that poor economic conditions significantly impair teaching effectiveness, research output, and instructional delivery. The study links productivity and performance to teaching quality outcomes, addressing implications for curriculum delivery and student learning.